Pelatihan Pengenalan Dasar Linux Ubuntu 22.04 LTS di Pusat Pendidikan Manajemen Bisnis “Mitra Kreatif Computer” Kisaran - Siagiaan, Edward Robinson (Jurnal Masyarakat Indonesia (Jumas), 2023)
Community Service activities are carried out at the Business Management Education Centre "Mitra Kreatif Computer" Kisaran in the form of training on the introduction of an operating system application for junior and senior high school students in the Kisaran area. This institution is located at Jl. Cokroaminoto No. 115 B Kisaran. There are many people who do not have the right job or business, so it is difficult to get a job at this time, this is a big problem faced by prospective workers who have just completed high school level studies in improving the economy, especially in the situation facing the economic recession in 2023. Previously the Business Management Education Centre "Mitra Kreatif Computer" Kisaran provided learning and training materials to the community with a variety of skills. Such as graphic design training, computer engineering and others. The training that will be carried out is training in the introduction of an operating system application for junior and senior high school students in the Kisaran area. With this training course, it can help the community to get a job or open business opportunities. Evaluation of learning outcomes is carried out directly after the training is completed, by giving exam questions or quizzes by setting the time tempo. The questions/quizzes are in the form of design examples and will be done by each participant then saved and displayed on the projector, then the instructor scores and submits the score to the admin of the Business Management Education Centre "Mitra Kreatif Computer" Kisaran to print the certificate and give it to the trainee.